AS RELAÇÕES DE GÊNERO ALÉM DAS PÁGINAS DE QUERIDA: A REVISTA E SUAS LEITORAS IRATIENSES ENTRE O TRADICIONAL E O MODERNO DURANTE A DÉCADA DE 1960 - Grochoski, Cibeli (2020)
This dissertation analyzes the representations of gender roles in the women's magazine Querida, published by Rio Gráfica Editora, belonging to the Globo Group, the analyzed journals were published during the 1960s. In this study, we tried to understand what was the representation that the magazine brought to respect for the “modern woman”, giving her traditional and conservative values and representations that define gender relations. The 60's are marked by the period in which Brazilian society was becoming modern, also integrating the period known as the Golden Years (1945-1964). Here, we seek to understand the participation of the journal's speeches, in the constitution of the subjectivities of women, readers. For this, the oral history methodology was used when interviewing iratienses women who read this magazine, during the studied decade. In addition to women, a man was interviewed, his report was important to deepen our view of masculinities. With the oral methodology, we entere the sociability spaces of the readers of the municipality of Irati - PR, who, during the 1960s, took speeches beyond magazines, dressed and behaved like “typical women of the Golden Years”, in its spaces of sociability, for example: schools, cinema, dances, with emphasis on the Spring Ball, in which the girls debuted with elegance, such as the standards of the time. We will also discuss the concept of representation, reading and readers, in the light of the discussions developed by historian Roger Chartier, having the magazine as a format of the region where there are tactics and strategies, according to Michel de Certeau. In order to address the history of women and studies of gender relations, we have the contribution of historians Michelle Perrot and Joan Scott. In addition to other authors, such as Pierre Bourdieu, Michel Foucault, Alistair Thompson, Alessandro Portelli, Tania Regina de Luca, Maria Celeste Mira, among other researchers and researchers, important theoretical and methodological references for this work.